Classification of medication incidents associated with information technology. (24th September 2013) - Cheung, Ka-Chun; van der Veen, Willem; Bouvy, Marcel L; Wensing, Michel; van den Bemt, Patricia M L A; de Smet, Peter A G M
Abstract: Introduction Information technology (IT) plays a pivotal role in improving patient safety, but can also cause new problems for patient safety. This study analyzed the nature and consequences of a large sample of IT-related medication incidents, as reported by healthcare professionals in community pharmacies and hospitals. Methods The medication incidents submitted to the Dutch central medication incidents registration (CMR) reporting system were analyzed from the perspective of the healthcare professional with the Magrabi classification. During classification new terms were added, if necessary. Main measures The principal source of the IT-related problem, nature of error. Additional measures: consequences of incidents, IT systems, phases of the medication process. Results From March 2010 to February 2011 the CMR received 4161 incidents: 1643 (39.5%) from community pharmacies and 2518 (60.5%) from hospitals. Eventually one of six incidents (16.1%, n=668) were related to IT; in community pharmacies more incidents (21.5%, n=351) were related to IT than in hospitals (12.6%, n=317). In community pharmacies 41.0% (n=150) of the incidents were about choosing the wrong medicine. Most of the erroneous exchanges were associated with confusion of medicine names and poor design of screens. In hospitals 55.3% (n=187) of incidents concerned human–machine interaction-related input during the use of computerized prescriber order entry. These use problems were also a major problem in pharmacy information systems outside the hospital. Conclusions A large sample of incidents shows that many of the incidents are related to IT, both in community pharmacies and hospitals. The interaction between human and machine plays a pivotal role in IT incidents in both settings.